Bulk Carbonate Sulfur Isotopic Composition of Carbonate Associated Sulfate in Squeeze Cake Residues from IODP Site U1553 on the southern Campbell Plateau - Alex Reis; Vanessa Fichtner; Andrea M Erhardt (PANGAEA, 2023)
Carbonate associated sulfate sulfur isotope results from IODP Site U1553 (166°11.4801'E, 52°13.4294'S) located on the Campbell Plateau are presented. Pore water and bulk carbonate samples collected during IODP Expedition 378 at Site U1553 in January 2020 were used for this study. The sediment samples were prepared using a 4-day digestion outlined in Wotte et al., 2012 which sequentially removed the water-soluble sulfate until only the carbonate associated sulfate (CAS) remained in the sediment. The CAS was extracted using a 10% HCl solution and then precipitated out of solution by adding 10% BaCl2 to precipitate the CAS as barite. Sulfur isotopes in from the CAS samples were analyzed using an EA-Isolink elemental analyzer connected in continuous flow to a MAT253 IRMS and the oxygen isotopes in dissolved sulfate were measured using a thermal conversion elemental analyzer connected in continuous flow to a Delta V IRMS. Analytical precision was measured using repeated measurements of a blind standard with an average 2-sigma of 0.4 extperthousand for sulfur isotopes (IAEA-SO-5). These data were collected to examine the impact of a long-duration (~26-million-year) unconformity has on the fidelity of the carbonate geochemical archive.